Pengungkapan Corporate Social Responsibility dan Price to Book Value : Pengujian Efek Moderasi Good Corporate Governance - Naraswari, Ni Made Ardi; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 31 No 11 (2021), 2021)
Price to book value (PBV) is a comparison between the stock price and the book value per share. This study aims to empirically examine the effect of corporate social responsibility disclosure on price to book value and the role of good corporate governance in strengthening the effect of corporate social responsibility disclosure on price to book value. The sample was determined by using nonprobability sampling method with purposive sampling technique. From purposive sampling, 19 samples were obtained from 2016-2019, so that 52 observations were obtained. The analysis technique used is moderated regression analysis (MRA). The results of the analysis show that the disclosure of corporate social responsibility has a negative and insignificant effect on price to book value and good corporate governance strengthens the effect of corporate social responsibility disclosure on price to book value. Keywords : Corporate Social Responsibility Disclosure; Price to Book Value; Good Corporate Governanance.